2011
DOI: 10.1021/ja2042035
|View full text |Cite
|
Sign up to set email alerts
|

Rational Catalysis Design on the Basis of Mechanistic Understanding: Highly Efficient Pd-Catalyzed Cyanation of Aryl Bromides with NaCN in Recyclable Solvents

Abstract: Rational catalysis design on the basis of a detailed mechanistic understanding has been used to successfully develop the first efficient general Pd-catalyzed aromatic cyanation reaction under the highly sought after practicable conditions: (i) MCN (M = Na or K) as a cyanide source; (ii) low-boiling recyclable solvents; and (iii) minimal quantities of inexpensive, nontoxic promoters. The developed catalytic reaction converts aromatic bromides to the corresponding nitriles in 88-99% isolated yield with NaCN and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
76
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(78 citation statements)
references
References 66 publications
1
76
0
1
Order By: Relevance
“…[5] Despite great advances, [1, 6] cross-coupling procedures to form ArCN have obtained a reputation as being highly irreproducible. [7] Mechanistic studies by Grushin have shown this is due, in part, to catalyst deactivation by cyanide, which is able to poison all of the intermediates in the catalytic cycle. [8] Common methods to avoid catalyst poisoning include the addition of reducing agents [9] or exploiting the low solubility of NaCN, KCN, and Zn(CN) 2 in organic solvents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Despite great advances, [1, 6] cross-coupling procedures to form ArCN have obtained a reputation as being highly irreproducible. [7] Mechanistic studies by Grushin have shown this is due, in part, to catalyst deactivation by cyanide, which is able to poison all of the intermediates in the catalytic cycle. [8] Common methods to avoid catalyst poisoning include the addition of reducing agents [9] or exploiting the low solubility of NaCN, KCN, and Zn(CN) 2 in organic solvents.…”
mentioning
confidence: 99%
“…[8] Common methods to avoid catalyst poisoning include the addition of reducing agents [9] or exploiting the low solubility of NaCN, KCN, and Zn(CN) 2 in organic solvents. Grushin's NaCN method, [7] while of high industrial relevance, requires the use of rigorously anhydrous conditions (glovebox setup), which renders this chemistry inconvenient or inaccessible to many synthetic chemists. Further, MCN salts (M = Na or K) are often milled prior to their use in order to guarantee solubility and reproducibility in their application.…”
mentioning
confidence: 99%
“…1 Typical strategies for the synthesis of aryl nitriles involve the Rosenmund-von Braun, [2][3] Sandmeyer, 4 and Schmidt 5 reactions. Recent advances show that the cross-coupling between aryl (pseudo)halides and various cyanide sources such as NaCN, 6 KCN, 7 CuCN, 8 TMSCN, 9 Zn(CN) 2 and acetone cyanohydrin 18 is also an alternative way to aryl nitriles. Furthermore, metal-catalyzed direct cyanation of aromatic C-H bonds has emerged as a useful alternative, owing to its potential atom-and step-efficient advance.…”
Section: Introductionmentioning
confidence: 99%
“…Other catalysts based on Pd(OAc) 2 or [Pd 2 dba 5 ] [9] precursors and various ligands, including PPh 3 , o-Tol 3 P, Cy 3 P, tBu 3 P, dppe, dppp, dppb, dppf, rac-BINAP, iPr-Xantphos, tBu-Xantphos, and DPEphos were inefficient. We were delighted to find, as a result of these exploratory runs, that Pd/Xantphos is an excellent catalyst for azidocarbonylation of iodobenzene.…”
mentioning
confidence: 99%
“…Reaction conditions: ArI (1 mmol), NaN 3 (1.2 mmol), [Pd 2 dba 5 ][9] (0.01 mmol; 2 mol % Pd), Xantphos (2 mol %) in THF (2 mL), hexanes (1 mL), and water(3 mL) at 23 8C. Reaction conditions: ArI (1 mmol), NaN 3 (1.2 mmol), [Pd 2 dba 5 ][9] (0.01 mmol; 2 mol % Pd), Xantphos (2 mol %) in THF (2 mL), hexanes (1 mL), and water(3 mL) at 23 8C.…”
mentioning
confidence: 99%